2005
DOI: 10.1371/journal.pbio.0030298
|View full text |Cite
|
Sign up to set email alerts
|

Malaria Infection Increases Attractiveness of Humans to Mosquitoes

Abstract: Do malaria parasites enhance the attractiveness of humans to the parasite's vector? As such manipulation would have important implications for the epidemiology of the disease, the question has been debated for many years. To investigate the issue in a semi-natural situation, we assayed the attractiveness of 12 groups of three western Kenyan children to the main African malaria vector, the mosquito Anopheles gambiae. In each group, one child was uninfected, one was naturally infected with the asexual (non-infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
246
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 313 publications
(255 citation statements)
references
References 16 publications
7
246
0
2
Order By: Relevance
“…C. obsoletus followed by Culicoides pulicaris L. 1758 was also the most abundant species found on horses (Van der Rijt et al, 2008). Van der Rijt et al (2008) also reported that host infectious status affects host location by vectors, as suggested by Torres-Estrada and Rodriguez (2003) and Lacroix et al (2005). C. obsoletus also seemed to be attracted to heifer, goat and ewe, as well as birds (Viennet et al, 2013), although this species is considered to be strictly mammalophilic (Lassen et al, 2012).…”
Section: Discussionmentioning
confidence: 97%
“…C. obsoletus followed by Culicoides pulicaris L. 1758 was also the most abundant species found on horses (Van der Rijt et al, 2008). Van der Rijt et al (2008) also reported that host infectious status affects host location by vectors, as suggested by Torres-Estrada and Rodriguez (2003) and Lacroix et al (2005). C. obsoletus also seemed to be attracted to heifer, goat and ewe, as well as birds (Viennet et al, 2013), although this species is considered to be strictly mammalophilic (Lassen et al, 2012).…”
Section: Discussionmentioning
confidence: 97%
“…Vector-borne disease agents can increase the frequency or duration of the contacts between vectors and hosts, suppress vector reproductive investment (an effect that is likely to increase nutrient reserves in the vector that are available for the parasite), or increase vector longevity (Hurd, 2003). For example, mosquitoes (Anopheles gambiae) that carry the malaria parasite, Plasmodium falciparum, feed longer and are more prone to bite several people per night than P. falciparum-free mosquitoes (Koella et al, 1998;Smallegange et al, 2013), whereas malaria infection in humans, mice and birds, enhances their attractiveness to the mosquitoes (Lacroix et al, 2005;Cornet et al, 2013;De Moraes et al, 2014).…”
Section: Zombie Ants Fearless Rats and Other Prominent Cases Of Manmentioning
confidence: 99%
“…First, the pathogen causes nutritional changes in infected plants, resulting in improved fitness of the vectors. Second, the pathogen increases plant attractiveness and suitability to the vectors by overcoming plant defenses against the vector species, thereby promoting vector performance and increasing pathogen spread (Beanland et al, 2000;Eigenbrode et al, 2002;Lacroix et al, 2005;Jiu et al, 2007;Wang et al, 2012;Luan et al, 2014). To date, only a few reports have examined the host plant genes that are involved in pathogen-vector-plant interactions.…”
Section: Introductionmentioning
confidence: 99%